Szkolenia i rozwój zawodowy "utalentowanych" pracowników - Szłapińska, Joanna (Wydawnictwo Naukowe UAM, 2012)
This article is to present a relatively new trend in human resources management, talent management in organizations. This work includes designing and implementing individual career paths as well as trainings and employee vocational development. The article deals with some problems with lifelong learning. The author presents the latest research concerning the adult participation in trainings. The article contains examples of case studies carried out in companies where the author did monographic research referring to high potential development programs.
Training and vocational development of talented employees
Keywords: Lifelong learning; vocational training; vocational development; talent management; core people; high potentials development programs